2018
DOI: 10.3329/jbau.v16i1.36473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen fertilizer and weed management on the yield of transplant aman rice

Abstract: The research work was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during aman season from July to December, 2015 to study the effect of nitrogen fertilizer and weed management on the growth and yield of transplant aman rice cv. BRRI dhan46. The experiment consisted of four fertilizer treatments viz. 0 kg N ha −1 (N 0 ), 40 kg N ha −1 (N 1 ), 80 kg N ha −1 (N 2 ) and 120 kg N ha −1 (N 3 ) and four weeding treatments viz. one hand weeding at 20 DAT (W 1 ), two hand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 4 publications
9
11
1
Order By: Relevance
“…Interaction effect of nitrogen fertilizer and weed management did not show significant effect on 1000-grain weight (Adhikari et al, 2018). Weight of 1000 grain was not significantly influenced by the interaction of weeding regime and integrated nutrient management in the present study.…”
Section: -Grain Weight (G)contrasting
confidence: 67%
See 3 more Smart Citations
“…Interaction effect of nitrogen fertilizer and weed management did not show significant effect on 1000-grain weight (Adhikari et al, 2018). Weight of 1000 grain was not significantly influenced by the interaction of weeding regime and integrated nutrient management in the present study.…”
Section: -Grain Weight (G)contrasting
confidence: 67%
“…But in the present study it is observed that plant height was not significantly influenced by the interaction between weeding regime and integrated nutrient management. Interaction effect of nitrogen fertilizer and weed management did not illustrate significant effect on final plant height (Adhikari et al, 2018).…”
Section: Plant Height (Cm)mentioning
confidence: 78%
See 2 more Smart Citations
“…Nitrogen nutrient acts as a major part of protoplasm, protein and chlorophyll. It also plays a remarkable role in increasing cell size which in turn increases yield [4]. For better grain development it is required to use adequate amount of nitrogen at early, at mid-tillering and at panicle initiation stage [5].…”
Section: Introductionmentioning
confidence: 99%